2020
DOI: 10.1002/cm.21628
|View full text |Cite
|
Sign up to set email alerts
|

The function of SEC22B and its role in human diseases

Abstract: Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins are a large protein complex that is involved in the membrane fusion in vesicle trafficking, cell growth, cytokinesis, membrane repair, and synaptic transmission. As one of the SNARE proteins, SEC22B functions in membrane fusion of vesicle trafficking between the endoplasmic reticulum and the Golgi apparatus, antigen cross-presentation, secretory autophagy, and other biological processes. However, apart from not being SNARE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 106 publications
(138 reference statements)
0
21
0
Order By: Relevance
“…Table 5B). Interestingly, SNARE protein SEC22B has been shown to modulate many pathological and physiological processes including autophagy, vesicle trafficking, neurodegeneration, cancers as well as infectious diseases (Sun et al, 2020). SEC22B is closely related to tumorigenesis and has been confirmed in numerous cancers including lung, breast, prostate, and uterine cancers (Gao et al, 2013), and furthermore, SEC22B has been shown to fuse with NOTCH2 and was confirmed in aggressive breast cancer (Veeraraghavan et al, 2016).…”
Section: Our Novel Findings Are Further Validated By Omics Datamentioning
confidence: 99%
“…Table 5B). Interestingly, SNARE protein SEC22B has been shown to modulate many pathological and physiological processes including autophagy, vesicle trafficking, neurodegeneration, cancers as well as infectious diseases (Sun et al, 2020). SEC22B is closely related to tumorigenesis and has been confirmed in numerous cancers including lung, breast, prostate, and uterine cancers (Gao et al, 2013), and furthermore, SEC22B has been shown to fuse with NOTCH2 and was confirmed in aggressive breast cancer (Veeraraghavan et al, 2016).…”
Section: Our Novel Findings Are Further Validated By Omics Datamentioning
confidence: 99%
“… Horikoshi et al (2013 ) reported that variants in ADCY5 were associated with lower birth weight in the European population, implying that ADCY5 may be linked to a poor maternal–fetal environment. Furthermore, SEC22A, also known as a vesicle-trafficking protein SEC22 homolog B, is involved in vesicle trafficking and regulates multiple signaling and transportation pathways ( Sun et al, 2020 ). In an animal model, SEC22A was found to be over-expressed in immature oocytes compared to matured counterparts, indicating a potential effect of SEC22A in oocyte growth and maturation ( Mamo et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…No specific association with cancer-related processes has been reported to date for this gene; however, it has been demonstrated that vesicle trafficking plays a crucial role in tumorigenesis [47]. Moreover, its homolog SEC22B (SEC22 homolog B, vesicle trafficking protein) is involved in carcinogenesis and harbors several mutations associated with different cancer models [48]. VAMP3 (vesicle associated membrane protein 3) encodes a member of the vesicle-associated membrane protein (VAMP)/synaptobrevin family and is involved in integrin trafficking and cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…For the migration assay, cells (1 × 10 4 per well) were seeded, and reverse transfected in an Oris Cell Migration Assay 96-well plate after insertion of Oris Cell Seeding Stoppers. Stoppers were removed 24 h after transfection (T0) and migration was evaluated at different time points (24,48,72,96, and 144 h after stopper removal). Cells migrated in the detection zone were quantified by using ImageJ software.…”
mentioning
confidence: 99%